Acute abdominal pain in non-pregnant endometriotic patients: not just dysmenorrhoea. A systematic review. (2nd January 2021) - Mabrouk, Mohamed; Borghese, Giulia; Esposti, Eugenia Degli; Raimondo, Diego; Remorgida, Valentino; Arena, Alessandro; Zupi, Errico; Mattioli, Giulia; Ambrosio, Marco; Seracchioli, Renato
Abstract: Endometriosis, defined as the presence of functional endometrial tissue outside the uterine cavity, presents mainly with pelvic pain and infertility. Acute abdominal pain in non-pregnant patients with endometriosis might be minimised as a typical feature of the disease, while endometriosis is rarely considered in the differential diagnosis of acute abdominal pain. Our objective was to conduct a systematic review of the current literature of cases of acute abdomen/acute abdominal pain in non-pregnant endometriotic patients. We performed a PubMed/MEDLINE search of studies published from January 1990 to December 2018, selecting English language reports and series of non-pregnant patients with acute abdomen and histological confirmation of endometriosis. The studies were revised by two independent authors. Data were abstracted and compiled for analysis. Fifty articles reporting 62 patients were identified. The complications were classified according to anatomical sites in bowel, urinary tract, and genital organs emergencies. Rarely was the first diagnostic hypothesis endometriosis, misdiagnosis was frequent. The time frame from symptoms onset to management was often long. This is the first systematic review evaluating acute abdomen/acute abdominal pain in non-pregnant endometriotic patients. These conditions are rare but possibly life-threating and require prompt diagnosis and emergent medical or surgical treatment.